Brazing process and high-temperature performance of SUS410/Hastelloy X joint - Yuanbin LI; Hao SUN; Xingdong CHEN; Wei FU; Xiaoguo SONG (Hanjie xuebao)
The vacuum brazing of SUS410 stainless steel to Hastelloy X dissimilar materials was successfully executed utilizing BNi-2 adhesive tape as the brazing alloy. The microstructure of the brazed joint interface was analyzed using an energy dispersive spectrometer (SEM) and an energy dispersive spectrometer (EDS). The influence of brazing duration on the interfacial microstructure and mechanical properties was investigated. In order to evaluate the high-temperature service performance of the joint, the influence of high-temperature (620 ℃) aging on the interface microstructure and high-temperature mechanical properties of the joint was studied. The results show that the typical interface structure of the brazed joint is SUS410/α-Fe+(Fe, Cr)-B/Ni(s, s)+Cr-B/γ-phase+(Ni, Cr, Fe)-B+(Cr-B, Mo-B)/Hastelloy X. As brazing continues, the shear strength of the joint first increases and then decreases. When the brazing temperature is 1 100 ℃, and the holding time is 10 minutes, the joint achieves the maximum shear strength of 216.8 MPa. The fracture is a ductile one. After aging at 620 ℃, the area of the diffusion zone at the joint has significantly increased, and this increase continues to grow over time. After the aging, the distribution of borides at the grain boundaries within the diffusion zone of the joint becomes more uniform, and the aggregation degree at the grain boundaries decreases. As aging continues, the shear strength at high temperature (620 ℃) gradually converges to 138.2–145.9 MPa, reaching 63.7%–67.3% of the shear strength at room temperature.